2011
DOI: 10.2215/cjn.01410211
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Renal Transplantation Patients with Henoch-Schönlein Purpura

Abstract: SummaryBackground and objectives Although Henoch-Schö nlein purpura (HSP) is the most common form of renal vasculitis in childhood, progression to ESRD is rare, and there are few data on outcomes of renal transplantation in patients with HSP.Design, setting, participants, & measurements This is a matched retrospective cohort study of renal allografts using the United Network of Organ Sharing database (1987 to 2005). Of the 189,211 primary renal allografts, there were 339 with a diagnosis of HSP. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 30 publications
(20 reference statements)
1
22
0
Order By: Relevance
“…A retrospective cohort study by Nada et al ., including 43 HSPN patients from six transplant centres in Belgium and France, reported similar overall graft survival rates of HSPN (84% and 66% at 5 and 10 years, respectively) compared with the present analyses (86% and 68% at 5 and 10 years, respectively). Also, in keeping with the findings of the present study, comparable death‐censored renal allograft survival was observed between ESKD patients with either local or HSPN in matched case–control studies from the United Network of Organ sharing database (58.4% and 59.3% at 10 years, P = 0.57) …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A retrospective cohort study by Nada et al ., including 43 HSPN patients from six transplant centres in Belgium and France, reported similar overall graft survival rates of HSPN (84% and 66% at 5 and 10 years, respectively) compared with the present analyses (86% and 68% at 5 and 10 years, respectively). Also, in keeping with the findings of the present study, comparable death‐censored renal allograft survival was observed between ESKD patients with either local or HSPN in matched case–control studies from the United Network of Organ sharing database (58.4% and 59.3% at 10 years, P = 0.57) …”
Section: Discussionsupporting
confidence: 91%
“…Also, in keeping with the findings of the present study, comparable death-censored renal allograft survival was observed between ESKD patients with either local or HSPN in matched case-control studies from the United Network of Organ sharing database (58.4% and 59.3% at 10 years, P = 0.57). 28 The strengths of this study included its very large sample size, inclusiveness and long duration of follow-up. We included both HSPN and kidney-limited IgAN patients receiving RRT in Australia and New Zealand during the study period from 1971 to 2012 and reported observations from a contemporary cohort (1998-2012) as the primary results.…”
Section: Renal Transplant Patient Survivalmentioning
confidence: 99%
“…They also found that mean GFR was similar in patients with and without biopsy‐proven HSN recurrence. In a matched retrospective cohort study based on the analysis of 339 HSN recipients from the UNOS database, the frequency of graft loss related to HSN recurrence was estimated at 13.6% [119]. In this study, renal graft survival at 10 years did not differ significantly between the HSN group and patients undergoing transplantation for IgA nephropathy (58.4% and 59.3%, respectively).…”
Section: Secondary Glomerulonephritismentioning
confidence: 65%
“…Compared with IgAN, relatively little is known about recurrent IgA vasculitis in renal allografts. The recurrence rate ranges from 15 to 53%, and graft loss due to recurrent IgA vasculitis was 7.5-28.6% in different observation periods [133][134][135]. A large casecontrolled study of 318 patients from one center showed no difference in 10-year graft survival between patients with IgAN recurrence and non-IgAN matched controls: 75% versus 82% [136].…”
Section: Recurrent Diseasementioning
confidence: 99%